Geologia e paleontologia de depósitos fossilíferos pleistocênicos do Rio Grande do Norte - Santos, Maria de Fátima Cavalcante Ferreira dos (2006)
This study deals with origin, sedimentary filling and fossil content of three tanks situated at Antônio Martins, Barcelona, Rui Barbosa, and Apodi counties, Rio Grande do Norte State. In addition, fossil materials from the Câmara Cascudo Museum - UFRN - Fundação Amigos do Lajedo Soledade - FALS, and from private ownership were investigated. The following families were identified: Megatberiidae, Gomphotheriidae, Mylodontidae, Equidae, Felidae, Canidae, Hydrochoeridae, Camelidae, Cervidae, Dasypodidae, Glyptodontidae, Macraucheniidae, Toxodontidae, and an undetermined Edentata Pilosa. The megafauna analysis indicated that herbivorc families occur mainly in tanks, whereas carnivore families occur in a vast proportion in an investigated ravine. Taphonomie analyses were limited to physical features because the vast majority of fossils were previously colleted without appropriate care for this kind of study. The main fossization processes were identified during diagenetie investigation. Permineralization is the most important process and replacement is the secondary one during fossilization. The study concluded that paleoenvironmental conditions during the late Pleistocene were more humid than the current one. Tropical savana, characterized by fields and cerrados , was the dominant vegetation